Effects of dietary chromium picolinate supplementation on performance and plasma concentrations of insulin and corticosterone in laying hens under low ambient temperature - Şahin, Kazım; Küçük, Ömer; Şahin, Nurhan (Blackwell Wissenschafts-Verlag Gmbh, 2001)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate) on performance and plasma concentrations of insulin and corticosterone of laying hens (Ross Brown) under a low ambient temperature (6.9 degreesC). One hundred and twenty laying hens (46 weeks old) were divided into four groups, 30 hens per group. The laying hens were fed either a control diet containing 710.3 p.p.b. chromium or the control diet supplemented with 100, 200 or 400 mug chromium/kg diet. increasing supplemental chromium increased live weight change (p less than or equal to 0.001, linear) and egg production (p less than or equal to 0.001, linear) and also improved feed efficiency linearly (p less than or equal to 0.001). Live weight change and egg production also had quadratic responses (p less than or equal to 0.001) to increasing chromium supplementation. Plasma insulin concentration increased linearly (p less than or equal to 0.001), whereas corticosterone concentration decreased linearly (p less than or equal to 0.001) as dietary chromium supplementation increased. The results of this study indicate that supplemental dietary chromium, 200 p.p.b. in particular, had a positive effect on performance and increased the plasma insulin concentration of laying hens under cold stress.
Keywords: Stressed Feeder Calves; Immune-Responses; Carcass Traits; Metabolism; Serum; Glucose; Broilers; Basal